One-pot sol-gel preparation for efficient cobalt-molybdenum-titania hydrotreating catalysts - Nguyen, D. L.; Gillot, S.; Souza, D. O.; Blanchard, P.; Lamonier, Carole; Berrier, E.; Kotbagi, T. V.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Cristol, S.; Payen, E.; Lancelot, Christine (Chemcatchem, 2012)
Titania-based hydrodesulfurization catalysts were prepared by using a one-pot solgel method with the titanium peroxo complex as titanium precursor and molybdenum and cobalt precursors dissolved in the aqueous hydrogen peroxide solution used during synthesis. Catalysts with MoO3 loadings varying from 5 to 40 wt?% and a Co/Mo atomic ratio of 0.5 were prepared. Solids with molybdenum loadings below 20 wt?% MoO3 demonstrated poor hydrodesulfurization activity for the model compound thiophene. This was attributed to the presence of a large amount of embedded cobalt and molybdenum species in the titania matrix. A significant increase in the catalytic activity was observed for solids containing 20 and 25 wt?% of MoO3 on which active species appeared to be accessible on the titania surface. Furthermore, the highest conversion obtained on these solgel solids was superior to the highest conversion obtained on reference catalysts prepared through the impregnation of ammonium heptamolybdate and cobalt nitrate on commercial titania.
Keywords: cobalt; heterogeneous catalysis; Molybdenum; sol-gel process; titanium